Решите уравнение 1) (x+9)/3-1=x/5 2) (x-6)/4-1=x/3 3) (x+1)/2-(2+x)/4=3 4) (2x-3)/3-(x-5)/4=2 5) 1/3*(4x-1)=x+7 6) 1/7*(8x+3)=x-1

Решите уравнение 1) (x+9)/3-1=x/5 2) (x-6)/4-1=x/3 3) (x+1)/2-(2+x)/4=3 4) (2x-3)/3-(x-5)/4=2 5) 1/3*(4x-1)=x+7 6) 1/7*(8x+3)=x-1
Гость
Ответ(ы) на вопрос:
Гость
2) (x-6)*3=3x 3x-18=3x 3x-3x=18 0=0 (нет ответ) 3) (2 (х+1)-2-х)/4=3 (2х+2-2-х)/4=3 х=12 4) (4 (2х-3)-3 (х-5))/12=2 (8х-12-3х+15)/12=2 (5х+3)/12=2 5х+3=24 5х=21 х=4 1/5=4,2 5) (4х-1)/3=х+7 4х-1=3х+21 х=20 6) (8х+3)/7=х-1 8х+3=7х-7 х=-10
Не нашли ответ?
Ответить на вопрос
Похожие вопросы